2021 11th IEEE International Conference on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applicat 2021
DOI: 10.1109/idaacs53288.2021.9661062
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Global Human Settlement Layer and NASA Population Data for Ukraine

Abstract: In Ukraine, due to financial difficulties, the planned census is often postponed from year to year. The country is forced to rely on static data, which is sometimes completely untrue. In addition, it is not possible to count the number of inhabitants everywhere. In particular, Ukraine has not known for several years exactly how many people live in the occupied territories. As a result -the wrong distribution of the budget, which entails another financial crisis and a number of other troubles. At the same time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For FUA calculation, the population data from two sources were used-the Global Human Settlement Layer (GHSL) by the European Commission (2022) [17]. Study [18] demonstrated that Global Human Settlement Layer data have a much higher correlation with statistical information on the population of Ukrainian cities.…”
Section: Population Datamentioning
confidence: 99%
“…For FUA calculation, the population data from two sources were used-the Global Human Settlement Layer (GHSL) by the European Commission (2022) [17]. Study [18] demonstrated that Global Human Settlement Layer data have a much higher correlation with statistical information on the population of Ukrainian cities.…”
Section: Population Datamentioning
confidence: 99%
“…For FUA calculation, the population data from two sources were used-the Global Human Settlement Layer (GHSL) by the European Commission (2015) [32] and NASA's population density product (2015 and 2020) [33]. A separate study [34] was conducted to perform the validation of population data from these sources, and it was concluded that Global Human Settlement Layer data have a much higher correlation with statistical information on the population of Ukrainian cities. However, if the calculations are made at the level of the whole country, both products can be used.…”
Section: Population Datamentioning
confidence: 99%